PERANCANGAN DAN PERHITUNGAN ELEMEN MESIN PENCETAK PELET MAGGOT SISTEM EXTRUDER - nuraini lusi (Techno Bahari, 2020)
Bioconversion has indeed begun to be developed a lot recently. Through this process, the nutrient content in organic waste can be formed into other forms of nutrients, namely biomass with the help of insect larvae, one of which is the insect larvae of Hermetia illucens / Black Soldier Fly (BSF). Larvae of this type are often used as bioconversion agents and are better known as "maggots". One example of its use is in the form of maggot pellets. From the results of the survey conducted, the tools used to make maggot pellets are still simple so that they produce pellets that are not optimal. The redesign of this maggot pellet molding machine will apply a single motor system for dual drives, namely the extruder shaft and the cutter shaft. The working mechanism of the maggot pellet molding machine is that when the machine is turned on, the screw shaft in the barrel will rotate according to the motor rotation and the dough from the feed hopper drops down into the barrel for processing. The dough that has been processed is then removed through the mold.